(untitled) (Journal of Population and Development, 2024)
This paper investigates the relationship between banks’ competition and nonperforming loans (NPLs), considering GDP per capita, gross savings, and domestic bank credit to the private sector. The study utilizes comprehensive secondary data from 1994 to 2022, scrutinizing diverse banking environments and revealing significant findings. The analysis reveals a significant positive correlation between the number of banks and the NPL ratio, indicating that increased competition leads to higher NPL. Nonetheless, banks’ domestic credit to the private sector has little effect on NPLs. The analysis also reveals a significant positive correlation between gross savings and the NPLs. Furthermore, higher NPLs ratio is linked to reduced commercial bank branches, lower capital adequacy ratios, and diminished bank liquidity reserves, posing potential financial stability risks. Even if large NPLs initially lower inflation rates, their long-term impacts depend on successful policy interventions. Additionally, NPLs significantly impact banks’ return on assets and net interest margins, necessitating effective profitability and risk management strategies. The study offers crucial insights for regulators, politicians, and banking professionals to understand the complexities of risk management and competition in the banking industry and create plans to lower NPLs.